R&D+I OF MEXICAN PUBLIC ENERGY RESEARCH CENTERS DURING ENERGY REFORMS FROM 2006-2024 (Nexo Revista Científica, 2025)
From 2006 to 2024, Mexico had presidents from different political parties, each with their own vision for managing energy resources, particularly oil and electricity. However, there was a convergence of ideas around two themes: modernizing the energy sector and promoting renewable sources. The objective of the Public Research Centers (PRCs) in the energy sector is to strengthen it by developing technologies based on current public policies. This paper aims to identify whether the PRCs modified patenting trends in accordance with the public policies (PPs) of each administration. Using qualitative research methodologies such as case studies and semi-structured interviews, it was found that there were no significant changes in the intellectual property protection trends of these centers. This paper is the product of a previous degree research project. It aims to publish some of the most relevant results of this extensive work.